1998
DOI: 10.1099/00221287-144-5-1443
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PhoP binding to the tuaA promoter with PhoP binding to other Pho-regulon promoters establishes a Bacillus subtilis Pho core binding site

Abstract: The phosphate-deficiency response in Bacillus subtilis is regulated by PhoP PhoR, a pair of two-component regulatory proteins. PhoR is a histidine kina and PhoP is a response regulator. Genetic evidence indicates that the Pho-regulon genes, which are induced or repressed under phosphate starvation conditions, are regulated by PhoP and PhoR at the transcriptional level. It has previously been shown that PhoP binds to four Pho-regulon promoters in both unphosphorylated and phosphorylated forms. This study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 26 publications
3
67
0
Order By: Relevance
“…A total of 267 proteins were significantly enriched [ t ‐test, P value ≀ 0.05, fold‐change (log2) ≄ 1.5] during Pi depletion and there was concordance between the two datasets. These enriched proteins included the transmembrane and ATP‐binding domains of the Pst system (PstC, PstA, PstB), a 2‐aminoethylphosphonate (2‐AEP)–specific phosphonatase (PhnX, PhnW) (Jiang et al ., 1995; Baker et al ., 1998; White and Metcalf, 2007), proteins involved in lipid remodelling (PlcP, DagK, OlsA, OlsB, Cfa, TauD) (Liu and Hulett, 1998; Antelmann et al ., 2000; Zavaleta‐Pastor et al ., 2010; Carini et al ., 2015; Sebastian et al ., 2016), a putative intracellular phosphatase (UxpA) and the twin‐arginine translocation (TAT) pathway (Putker et al ., 2013) (Table 2). Proteins for both starch (MalQ, GlgE, GlgX, GlpA and GlpB) and polyhydroxyalkanoic acid (PhaA, PhaG, PhaC) biosynthesis (carbon storage) were also enriched during Pi stress (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 267 proteins were significantly enriched [ t ‐test, P value ≀ 0.05, fold‐change (log2) ≄ 1.5] during Pi depletion and there was concordance between the two datasets. These enriched proteins included the transmembrane and ATP‐binding domains of the Pst system (PstC, PstA, PstB), a 2‐aminoethylphosphonate (2‐AEP)–specific phosphonatase (PhnX, PhnW) (Jiang et al ., 1995; Baker et al ., 1998; White and Metcalf, 2007), proteins involved in lipid remodelling (PlcP, DagK, OlsA, OlsB, Cfa, TauD) (Liu and Hulett, 1998; Antelmann et al ., 2000; Zavaleta‐Pastor et al ., 2010; Carini et al ., 2015; Sebastian et al ., 2016), a putative intracellular phosphatase (UxpA) and the twin‐arginine translocation (TAT) pathway (Putker et al ., 2013) (Table 2). Proteins for both starch (MalQ, GlgE, GlgX, GlpA and GlpB) and polyhydroxyalkanoic acid (PhaA, PhaG, PhaC) biosynthesis (carbon storage) were also enriched during Pi stress (Supporting Information Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in BIRD‐1 UDP‐glucose 6‐phosphate dehydrogenase (TuaD) was also PHO‐regulated. In B. subtilis , TuaD is encoded by the tua operon that is involved in the production of teichuronic acid lipids during Pi‐depletion (Liu and Hulett, 1998; Antelmann et al ., 2000). The rest of the genes required for teichuronic acid were absent, therefore, making the role of TuaD somewhat unclear in BIRD‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does switching from teichoic to teichuronic acids reduce the phosphorus requirement of the cell, but teichoic-acidcontaining cell wall released into the growth medium as a result of wall turnover (Merad et al, 1989) represents a significant potential source of phosphorus (Grant, 1979) that can be recovered by the combined activities of APases and APDases. We and others have shown that teichuronic acid biosynthesis in B. subtilis is under the control of the Pho regulon (Mu$ ller et al, 1997 ;Qi & Hulett, 1998 ;Liu & Hulett, 1998). The Pho regulon is regulated by a twocomponent signal transduction pathway consisting of proteins PhoP and PhoR (Seki et al, 1987(Seki et al, , 1988, equivalent to PhoB and PhoR of Escherichia coli, IP: 54.200.74.82…”
Section: Abbreviationsmentioning
confidence: 99%
“…Pst, a high-affinity phosphate ABC transporter (35), facilitates the uptake of P i at low P i concentrations. Concomitant repression of the teichoic acid operons (tagAB and tagDEF) and induction of teichuronic acid operon (tuaA to tuaH) conserves phosphate by bringing about the controlled replacement of the phosphate-containing cell wall polymer teichoic acid with the non-phosphate-containing teichuronic acid (21,24,28). The functions of five putative Pho regulon genes (ydhF, ykoL, yhaX, yhbH, and yttP) are presently unknown (2,32,36).…”
mentioning
confidence: 99%